3 Tesla MRI detects deterioration in proximal femur microarchitecture and strength in long‐term glucocorticoid users compared with controls. Issue 6 (12th June 2015) - Chang, Gregory; Rajapakse, Chamith S.; Regatte, Ravinder R.; Babb, James; Saxena, Amit; Belmont, H. Michael; Honig, Stephen
Abstract : Background: Glucocorticoid‐induced osteoporosis (GIO) is the most common secondary form of osteoporosis, and glucocorticoid users are at increased risk for fracture compared with nonusers. There is no established relationship between bone mineral density (BMD) and fracture risk in GIO. We used 3 Tesla (T) MRI to investigate how proximal femur microarchitecture is altered in subjects with GIO. Methods: This study had institutional review board approval. We recruited 6 subjects with long‐term (> 1 year) glucocorticoid use (median age = 52.5 (39.2–58.7) years) and 6 controls (median age = 65.5 [62–75.5] years). For the nondominant hip, all subjects underwent dual‐energy x‐ray absorptiometry (DXA) to assess BMD and 3T magnetic resonance imaging (MRI, 3D FLASH) to assess metrics of bone microarchitecture and strength. Results: Compared with controls, glucocorticoid users demonstrated lower femoral neck trabecular number (−50.3%, 1.12 [0.84–1.54] mm −1 versus 2.27 [1.88–2.73] mm −1, P = 0.02), plate‐to‐rod ratio (−20.1%, 1.48 [1.39–1.71] versus 1.86 [1.76–2.20], P = 0.03), and elastic modulus (−64.8% to −74.8%, 1.54 [1.22–3.19] GPa to 2.31 [1.87–4.44] GPa versus 6.15 [5.00–7.09] GPa to 6.59 [5.58–7.31] GPa, P < 0.05), and higher femoral neck trabecular separation (+192%, 0.705 [0.462–1.00] mm versus 0.241 [0.194–0.327] mm, P = 0.02). There were no differences in femoral neck trabecular thickness (−2.7%, 0.193 [0.184–0.217] mm versus 0.199 [0.179–0.210] mm, P = 0.94) or femoral neck BMD T‐scores (+20.7%, −2.1 [−2.8 to −1.4] versus −2.6 [−3.3 to −2.5], P = 0.24) between groups. Conclusion: The 3T MRI can potentially detect detrimental changes in proximal femur microarchitecture and strength in long‐term glucocorticoid users. J. MAGN. RESON. IMAGING 2015;42:1489–1496.